CONCEPTUALIZING AI-SUPPORTED EDUCATIONAL LEADERSHIP: A SYSTEMATIC LITERATURE REVIEW AND QUALITATIVE META-SYNTHESIS - Juhji Juhji; Teguh Fachmi; Supardi Supardi; Irfan Abbas (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The development of Artificial Intelligence (AI) has transformed educational leadership practices by improving decision-making, organizational governance, teacher professional development, and institutional transformation. Despite the significant increase in publications on AI in education, existing studies remain fragmented, generally discussing AI from separate perspectives, such as digital leadership, AI governance, teacher readiness, prompt literacy, and technology adoption. This study aims to synthesize research developments on AI-Supported Educational Leadership, identify key themes, uncover research gaps, and formulate an integrated conceptualization as a foundation for developing educational leadership theory and practice in the era of artificial intelligence. This study employed a Systematic Literature Review (SLR) approach, combined with qualitative meta-synthesis, following the PRISMA 2020 guidelines. A literature search was conducted through the Scopus database using keywords related to Artificial Intelligence and Educational Leadership. Articles were selected based on predetermined inclusion and exclusion criteria and analyzed using open coding, axial coding, and selective coding to produce a thematic and conceptual synthesis. The synthesis identified five main themes: strategic digital leadership, ethical AI governance, teacher readiness for AI, human-AI collaborative leadership, and strategic transformation of educational organizations. These five themes interact to form a conceptualization of AI-Supported Educational Leadership, which views AI as an organizational capability to strengthen leadership, organizational learning, institutional innovation, and the sustainability of educational performance. This study reveals that the existing literature remains dominated by the technology adoption perspective and has not fully explained the organizational mechanisms linking AI to the effectiveness of educational leadership. AI-Supported Educational Leadership is a leadership paradigm that integrates strategic leadership, responsible AI governance, teacher capacity development, organizational learning, and human-AI collaboration to support sustainable educational transformation. This perspective expands the concept of digital leadership by positioning AI as part of an organizational capability rather than merely an enabling technology. This study offers a conceptual synthesis that integrates various dimensions of leadership, organization, and artificial intelligence to conceptualize AI-Supported Educational Leadership. This conceptualization makes theoretical contributions to the development of the educational leadership literature while offering empirical research directions and strategic recommendations for educational leaders and policymakers to implement AI effectively, ethically, and sustainably.